Penggunaan Leksikon Allāh Sebagai Ekspresi Tuhan - Yuangga Kurnia Yahya (Indonesia Center for Middle East Studies, 2019)
This article discuss the history of translating Bibles from Greek into Arabic. Translation itself is an attempt to spread the Word of God to the whole world and facilitate the translation of these sacred texts. One of the prominent things in this translation is the form of God's expression. God's expression uses the 'Allah' lexicon in which the lexicon is often understood as a limited lexicon for the mention of God in Islam. This discussion will use Eugene Nida's translation theory regarding general translation rules. The Biblical translation theory uses a theory initiated by Glen G Scorgie, Mark L Strauss, and Steven M Voth regarding the challenge of communicating God's language into human language. The results of the study indicate that this translation movement has been carried out since the Umayyad period and was renewed in modern times by the Missionaries. The use of the God lexicon is an attempt to bring the term in the Bible closer to Arabic culture.